Kajian Pentingnya Stock Opname Dalam Pengembangan Koleksi Perpustakaan - Eke Wince (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2017)
Stock opname is a kind of activity in a library to recount and recheck its collection with the goal of which is to know the real amount of the collection. Stock opname is urgent to do in order to control so that the library can know exactly and evaluate its asset or information resources. Having done the program of stock opname, the library can make real data about its collection by which the library consider how to develop the farther collection. Because of the important of this activity in developing collection, a library is adviced or persuaded to do it regularly in a certain time. That is in order to fulfill the aims or the goals of the collection developmentof a library based on the needs of users and the policy of its institution.